MAINTENANCE ANALYSIS OF ANCHOR CHAIN AGAINST CORROSION RATE BY PAINTING METHOD - Maulana Noor, Fariz; Rulianto, Rizal (Department of Marine Engineering, Universitas Hang Tuah, 2024)
One of the damages to the anchor and its chain is caused by being exposed to various environmental loads from the sea every time the anchor is lowered or when the anchor is raised, so that gradually it will experience fatigue or fatigue due to dynamic loads that occur repeatedly in a long period of time.However, there has not been an analysis that combines anchor chain maintenance of the corrosion rate with the painting method and comparison between before painting and after painting. Therefore, the researchers proposed a study